Pharmacognostical Standardization and Hptlc Fingerprint of Crataeva Tapia Linn. SSP. Odora (Jacob.) Almeida Leaves - PATIL, A. G.; KOLI, S. P; PATIL, D. A.; NARESH CHANDRA (International Journal of Pharma and Bio Sciences, 2010)
Crataeva tapia Linn. ssp. odora (Jacob.) Almeida, a traditional medicinal plant, which is valued for its benefits in the management of urinary and inflammatory disorders. Leaves are externally rubefacient and used in rheumatism; internally they are given as febrifuge and tonic. The leaves also act as anti-periodic. The current study was therefore carried out to provide requisite pharmacognostic details about the leaves of C. tapia. Pharmacognostic evaluation included examination of morphological and microscopical characters; physicochemical properties, phytochemical analysis, fluorescence study and HPTLC finger print. The powder microscopy showed the presence of anomocytic stomata and spiral thickening. Phytochemical screening reported the presence of tannins, steroidal compounds, cardiac glycosides and alkaloids. The Rf value of 0.35 detected at 300 nm and 600 nm by qualitative densitometric HPTLC fingerprint, can be used as identifying marker for methanolic extract. The present study will provide the information with respect to identification and authentication of crude drug.